Characteristics of internal structure feature of ameloblastoma, and ameloblastic fibroma and fibro-odontoma on radiographic examination (a literature review) : Karateristik gambaran struktur internal pada ameloblastoma, dan ameloblastik fibroma dan fibro-odontoma melalui pemeriksaan radiografi (tinjauan pustaka) - Fadhlil Ulum A.R.; Suhardjo Sitam; Ria N. Firman; Lusi Epsilawati (Makassar Dental Journal, 2020)
Ameloblastoma and other odontogenic tumors, specifically ameloblastic fibroma and ameloblastic fibro-odontoma are conditionsofbenigntumorsoriginatingfromtheodontogenicapparatus.Ameloblastomasaretumorsofodontogenic epithelial origin, while the other two odontogenic tumors originate from involvement of the ephitelial layer and the ectomesenchymal layer.Radiographicexaminationofameloblastoma,ameloblasticfibroma,and ameloblastic fibro-odontoma provides several variations in the description of internal structures that vary according to the lesions type. Radiographic examinations of ameloblastoma, ameloblastic fibroma, and ameloblastic fibro-odontoma provides several variations in the description of internalstructuresthatvaryaccordingtotype. This literaturere view aim stodistinguish the three cases based on the description of specific internal structures seen in the results of radiographic examinations. It is found that there are differences in the picture of the internal structure of ameloblastoma, ameloblastic fibroma and ameloblastic fibro-odontoma. Ameloblastoma appears unilocular and multilocular radiolucent with distinctive patterns such as honeycomb, soap bubble, and web spiders. The internal structure of ameloblastoma is similar to ameloblastic fibroma, but can be distinguished from other radiographic features. Whereas ameloblastic fibro-odontomas are more specifically differentiated from their internal structures. It was concluded that there are differences in the internal structure of ameloblastoma with radiographically, ameloblastic fibroma and ameloblastic fibro-odontoma.